Customer Based Brand Equity: Evidence from the Soft Drink Industry in Pakistan (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2014)
This study aimed to investigate the impact of brand equity on consumer responses in soft drink industry. Endeavor is to improve the conceptualization of brand equity concept in Pakistan. The study seeks guidance from Kellers Customer Based Brand Equity (CBBE) Model regarding link between brand equity and customer response. The study was designed to test the hypotheses through measuring the dimensions of brand equity of soft drink industry. Data was collected through a structured questionnaire. Brand equity predictors help to create and build customer based brand equity (CBBE) through an inter link order. Brand quality, brand association and brand image emerge as vital factors to affect the growth of CBBE. However, brand loyalty shows insignificant impact on growth of CBBE in socioeconomic context of Pakistani customers.The research study was limited to Lahore, Sialkot, Gujranwala and Faisalabad with restricted sample. The study should have vital practical implications for practicing managers and marketing strategists in the industry. The research paper aimed to comprehend the effects of customers based brand equity (CBBE) on customer responses in the context of soft drink industry of Pakistan. This study should deliver valuable information for the organizations who desire to develop brand equity for their products.